GAYA KEPEMIMPINAN PEREMPUAN SEBAGAI PEJABAT PUBLIK DI LINGKUNGAN PEMERINTAH DAERAH KABUPATEN MINAHASA - Trifena Revangelista Mambu; Joyce J. Rares; Welly Waworundeng (Halu Oleo University, 2023)
The aim of this research is to examine the leadership style of women as public officials in the Minahasa Regency Regional Government. The method in this research is a qualitative method with persuasive, facilitative, contributive and transformational indicators. Data analysis uses a qualitative descriptive approach starting from data reduction, data presentation and data verification. The results of the data analysis show that the leadership styles practised by public officials within the Regional Government of Minahasa Regency are persuasive, facilitative, contributive and transformational. Of these four leadership styles, the persuasive leadership style approach is more dominant. In the persuasive leadership style, female leaders seek to persuade and inspire others. Persuasive leaders do not always use authority or power to achieve obedience but instead use trust and honesty to gain followers. Persuasive leadership also reflects an empathetic and other-oriented personality. Because leaders with a persuasive style can understand the needs and psychological conditions of their followers, they can convey messages and instructions in a way that is relevant and meaningful for each individual.